amoA-encoding archaea and thaumarchaeol in the lakes on the northeastern Qinghai-Tibetan Plateau, China - Yang, Jian; Jiang, Hongchen; Dong, Hailiang; Wang, Huanye; Wu, Geng; Hou, Weiguo; Liu, Weiguo; Zhang, Chuanlun; Sun, Yongjuan; Lai, Zhongping (Frontiers in Microbiology, 2013)
All known ammonia-oxidizing archaea (AOA) belong to the phylum Thaumarchaeota within the domain Archaea. AOA possess the diagnostic amoA gene (encoding the alpha subunit of ammonia monooxygenase) and produce lipid biomarker thaumarchaeol. Although the abundance and diversity of AEA in freshwater lakes have been well-studied, little is known about amoA gene-encoding archaea (AEA) ecology in saline/hypersaline lakes. In this study, the distribution of the archaeal amoA gene and thaumarchaeol were investigated in nine Qinghai-Tibetan lakes with a salinity range from freshwater to salt-saturation (salinity: 325 g/L). The results showed that the archaeal amoA gene was present in hypersaline lakes with salinity up to 160 g/L. The archaeal amoA gene diversity in Tibetan lakes was different from those in other lakes worldwide, suggesting Tibetan lakes (high elevation, strong ultraviolet, and dry climate) may host a unique AEA population of different evolutionary origin from those in other lakes. Thaumarchaeol was present in all of the studied hypersaline lakes, even in those where no AEA amoA gene was observed. Future research is needed to determine the ecological function of AEA and possible sources of thaumarchaeol in the Qinghai-Tibetan hypersaline lakes.